Low-Dimensional Solids - Bruce, D; O'Hare, D; Walton, R (John Wiley and Sons, 2010)
With physical properties that often may not be described by the transposition of physical laws from 3D space across to 2D or even 1D space, low-dimensional solids exhibit a high degree of anisotropy in the spatial distribution of their chemical bonds. This means that they can demonstrate new phenomena such as charge-density waves and can display nanoparticulate (0D), fibrous (1D) and lamellar (2D) morphologies. This text presents some of the most recent research into the synthesis and properties of these solids and covers: •Metal Oxide Nanoparticles. •Inorganic Nanotubes and Nanowires. •Biomedical Applications of Layered Double Hydroxides. •Carbon Nanotubes and Related Structures. •Superconducting Borides. Introducing topics such as novel layered superconductors, inorganic-DNA delivery systems and the chemistry and physics of inorganic nanotubes and nanosheets, this book discusses some of the most exciting concepts in this developing field. Additional volumes in the Inorganic Materials Book Series: •Molecular Materials. Functional Oxides. Porous Materials. Energy Materials. All volumes are sold individually or as comprehensive 5 Volume Set. © 2010 John Wiley and Sons, Ltd.